First outbreak of Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae in Germany - Wendt, Constanze; Schütt, Sabine; Dalpke, Alexander; Konrad, M.; Mieth, Markus; Trierweiler-Hauke, Birgit; Weigand, Markus A.; Zimmermann, Stefan; Biehler, K.; Jonas, D. (European journal of clinical microbiology & infectious diseases, 2010)
We report the first outbreak of Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae in Germany. The presence of KPC was confirmed by polymerase chain reaction (PCR). The KPC-encoding plasmid was analysed by transconjugation experiments, DNA sequencing, Southern blotting and isoelectric focussing. Typing was performed by pulsed-field gel electrophoresis (PFGE). An ertapenem-resistant K. pneumoniae with low minimum inhibitory concentrations (MIC) to other cabapenems (tested by the Vitek system) was isolated from the index patient in January 2008. A KPC-2 was identified after K. pneumoniae with identical susceptibility patterns had been isolated from two more patients. Despite the introduction of infection control measures, transmission occurred in five additional patients and three of the patients died from infections. The source of the outbreak strain remained unclear; however, the Tn4401-containing blaKPC-2 gene was similar to previously described isolates from Greece. Five months after the end of the outbreak, a KPC-K. pneumoniae was isolated from a patient who had been treated in Greece previously. Retrospectively, this patient was treated in November 2007 on the same unit as the index case. Typing revealed that all patients were colonised by the same strain. KPC-K. pneumoniae has been introduced to Germany possibly from Greece and transmission to other institutions is likely.
Gesehen am 03.11.2023